Characterization of Salmonella endolysin XFII produced by recombinant Escherichia coli and its application combined with chitosan in lysing Gram-negative bacteria - Zhang, Shuhang; Chang, Yan; Zhang, Qing; Yuan, Yingbo; Qi, Qingsheng; Lu, Xuemei (Microbial cell factories, 2022)
Salmonella is a common foodborne pathogen, which can cause intestinal diseases. In the last decades, the overuse of antibiotics has led to a pandemic of drug-resistant bacterial infections. To tackle the burden of antimicrobial resistant pathogens, it is necessary to develop new antimicrobial drugs with novel modes of action. However, the research and development of antibiotics has encountered bottlenecks, scientific hurdles in the development process, as well as safety and cost challenges. Phages and phage endolysins are promising antibacterial agents that can be used as an alternative to antibiotics. In this context, the expression of endolysin derived from different phages through microbial cells as a chassis seems to be an attractive strategy. In this study, a new endolysin from the Salmonella phage XFII-1, named XFII, was screened and obtained. The endolysin yield exceeded 100 mg/mL by heterologous expression from E. coli BL21 and short induction. The endolysin XFII exhibited high bactericidal activity at a concentration of 0.5 μg/mL and reduced the OD nm of EDTA-pretreated E. coli JM109 from 0.8 to 0.2 within 5 min. XFII exhibited good thermo-resistance, as it was very stable at different temperatures from 20 to 80℃. Its bactericidal activity could keep constant at 4 °C for 175 days. In addition, the endolysin was able to exert lytic activity in eutrophic conditions, including LB medium and rabbit serum, and the lytic activity was even increased by 13.8% in 10% serum matrices. XFII also showed bactericidal activity against many Gram-negative bacteria, including Salmonella, E. coli, Acinetobacter baumannii, and Klebsiella pneumoniae. Surprisingly, the combination of endolysin XFII and chitosan showed a strong synergy in lysing E. coli and Salmonella without EDTA-pretreatment, and the OD nm of E. coli decreased from 0.88 to 0.58 within 10 min. The novel globular endolysin XFII was screened and successfully expressed in E. coli BL21. Endolysin XFII exhibits a broad lysis spectrum, a rapid and strong bactericidal activity, good stability at high temperatures and under eutrophic conditions. Combined with chitosan, XFII could spontaneously lyse Gram-negative bacteria without pretreatment. This work presented the first characterization of combining endolysin and chitosan in spontaneously lysing Gram-negative bacteria in vitro.